Role of Optical Coherence Tomography Angiography (OCTA) in Anterior Ischemic Optic Neuropathy - Gunawan, Calista Nathasya; Nusanti, Syntia (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2025)
Introduction: Anterior ischemic optic neuropathy (AION) is the most common type of optic neuropathy with symptoms of sudden and painless visual field defect and vision loss. Although evaluating the nonperfusion areas of the vascular ischemia have traditionally been visualized through fluorescein angiography, OCTA has proven to be effective in noninvasively representing the retinal vascular network. This literature review aims to evaluate the quantitaive OCTA assessment of peripapillary vessel density (VD) changes in AION. Methods: Literature search was performed in four databases (PubMed, ScienceDirect, ProQuest, and Cochrane Library) from 2018 to 2022 to identify relevant articles. Five studies were included in this review. Results: All five studies on OCTA findings of NAION eyes reported a reduction in the vessel density of peripapillary capillary plexus when compared to either the healthy control eyes or the fellow unaffected eyes. OCTA reveals vascular changes in both forms, aiding prognosis and treatment. One study comparing NAION and AAION indicates reduced vessel density in NAION and AAION, with more severe abnormalities and reduction of vessel density in AAION. Conclusion: OCTA can visualize alterations in vascular density in both types of AION, AAION and NAION, with a notably more pronounced reduction in peripapillary vessel density observed in AAION. Keywords: anterior ischemic optic neuropathy, optical coherence tomography angiography, peripapillary vessel density